My Beloved: Mitford Years # 15 : a Mitford novel - Karon, Jan, 1937- (New York : G. P. Putnam's Sons, 2025)
"When Father Tim's wife, Cynthia, asks what he wants for Christmas, he pens the answer in a love letter that bares his most private feelings. Then the letter goes missing and circulates among his astonished neighbors. So much for private. Can a letter change a life? Ask Helene, the piano teacher who has avoided her feelings for a lifetime. Ask Hope, the village bookseller who desperately needs something that's impossibly out of reach. Or, if you'd like to know how a brush with death can be the portal to a happy marriage, Cynthia will tell you all about it. In My Beloved, Harley gets an important letter of his own; a broken heart teaches the Old Mayor, Esther Cunningham, a lesson long in coming; and thanks to Lace and Dooley, readers get what they've been waiting for: Sadie. Poignant, hilarious, and life-affirming, My Beloved sets a generous table for millions of readers who love these characters like family. With Karon's signature humanity shining through on every page, this is a season of life in Mitford you won't want to miss"-- Provided by publisher.
new book 2025 fall.
Keywords: Family; Holidays; Novels; Fiction; Christmas fiction